الأسماء الإلهية وعلاقتها بالعالم في فكر محيى الدين بن عربي: The Divine Names of Allah and its Relation to the Nature in the Thought of Muhy Al-Din bin ‘Arabi - Muhammad Amin, Muhammad Rifa`i (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
Many scholars and thinkers have interpreted and elaborated the names of Allah SWT. However, the views expressed to these names relate only to the obedience of Allah and its effect to human behaviour. Only few of them associate the names of God with the existence of nature and the effects of these names on nature. Muhy al-Din Ibn ‘Arabi who popularized the term the oneness of existence was among those who used different methods in this aspect. This study attempts to expose Ibn ‘Arabi s efforts to link the names of Allah with the oneness of existence through the method of manifesting these names.